2018
DOI: 10.1016/j.envsci.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Road improvement enhances smallholder productivity and reduces forest encroachment in Ghana

Abstract: Impact of roads on farm size, market participation, and forest cover change in rural Ghana. MPhil thesis, James Cook University.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 109 publications
(189 reference statements)
1
27
0
1
Order By: Relevance
“…The presence of good road infrastructure and public transport reduces the transaction costs to farmers in the search for productivity-enhancing inputs. This corroborates findings of Acheampong, Sayer, and Macgregor (2018) who reported that access to improved roads encourage the use of modern farm inputs and thus higher yields. We are unable to confirm or reject the inverse productivity-size relationship in this study.…”
Section: Resultssupporting
confidence: 91%
“…The presence of good road infrastructure and public transport reduces the transaction costs to farmers in the search for productivity-enhancing inputs. This corroborates findings of Acheampong, Sayer, and Macgregor (2018) who reported that access to improved roads encourage the use of modern farm inputs and thus higher yields. We are unable to confirm or reject the inverse productivity-size relationship in this study.…”
Section: Resultssupporting
confidence: 91%
“…Analyzing existing livelihood strategies and outcomes in a specific context is primal because context shapes the opportunity structures within which livelihoods are constructed (Bebbington 1999 ). For example, how well an area is connected to markets, and the extent to which transportation facilities are accessible, may influence the livelihood strategies in an area (Acheampong et al 2018 ), and may mediate the mechanisms by which food crops and cash crops benefit household food security (Sibhatu and Qaim 2018 ). Moreover, the ability of households to engage in a type of livelihood strategy is influenced by the types of capital assets they have access to (Scoones 1998 ; Rakodi 1999 ).…”
Section: Background On the Relationships Between Livelihoods And Foodmentioning
confidence: 99%
“…Strategically planned roads, and the provisional infrastructure that often follows, may support this trend. Examples of increased accessibility leading to land-use stabilization exist, but are rarely documented (see Acheampong et al., 2018; Kaczan, 2017). Further research is required to evaluate empirical evidence on the policies and conditions that enable this transition (Ewers, Scharlemann, Balmford, & Green, 2009; Nanni et al., 2019; Rudel, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Combined with environmental protection policies, the transition from low productivity livelihood systems into more prosperous livelihoods can facilitate long-term conservation benefits (Muller & Zeller, 2002; Munroeaic, Southworth, & Tucker, 2002). In Ghana, Acheampong, Sayer, and Macgregor (2018) found that road improvement enhances smallholder productivity and thereby reduces forest encroachment. In India, Kaczan (2017) found road construction contributed to tree cover expansion, indicating the role of rural roads in facilitating reforestation.…”
Section: Introductionmentioning
confidence: 99%